Peran Pendidikan Dasar dalam Pembentukan Dasar Kemampuan Anak di SD Negeri 6 Wonogiri - Priska Dinanti Putri, Hana (Pendidikan Dasar dan Manajemen Pendidikan, 2023)
This article discusses the role of basic education in forming the basis of children's abilities. Primary education is an important foundation in children's development, influencing their intellectual, social and emotional skills. In this article, we explore how elementary education can help children develop cognitive abilities, interpersonal skills, and moral understanding. We also discuss factors that influence the effectiveness of basic education in shaping children's abilities, such as teaching methods, school environment, and the role of teachers. Additionally, we present empirical evidence supporting the importance of investing in basic education for the future of children and society as a whole.